2020
DOI: 10.1111/epi.16582
|View full text |Cite
|
Sign up to set email alerts
|

Defining the phenotype of FHF1 developmental and epileptic encephalopathy

Abstract: Objective: Fibroblast-growth-factor homologous factor (FHF1) gene variants have recently been associated with developmental and epileptic encephalopathy (DEE). FHF1 gene encodes a cytosolic protein that interacts with neuronal sodium channel. Aim of this study is to report the largest series of patients with pathogenic FHF1 genetic variants in order to define electro-clinical phenotype, genotype-phenotype correlation, and information about management and prognosis. Methods: Through an international collaborati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 41 publications
1
10
0
Order By: Relevance
“…The epilepsy in FHF1-DEE is often intractable but responsiveness to phenytoin (a sodium channel blocker) has been noted. [47][48][49] Individuals 3 and 4 in our series gained at least transient benefit from phenytoin. The other subjects have either not been given phenytoin or their response is unknown.…”
mentioning
confidence: 61%
See 1 more Smart Citation
“…The epilepsy in FHF1-DEE is often intractable but responsiveness to phenytoin (a sodium channel blocker) has been noted. [47][48][49] Individuals 3 and 4 in our series gained at least transient benefit from phenytoin. The other subjects have either not been given phenytoin or their response is unknown.…”
mentioning
confidence: 61%
“…FHF1-DEE is typically associated with focal epilepsy or a combined generalized and focal epilepsy. 48 Tonic seizures with autonomic signs are common in both FHF1-and FHF2-DEE. Other seizure types reported in both disorders include generalized tonic-clonic seizures, epileptic spasms, and absence and myoclonic seizures.…”
mentioning
confidence: 99%
“…Previously, missense variants or copy number variants (CNVs) in FG12 have been solely identified in patients with DEE. 16 Here we describe two additional patients, one with the recurrent variant G50S/G112S and a similar epileptic phenotype as described earlier 16 , and (which was not certified by peer review) is the author/funder. All rights reserved.…”
Section: Discussionmentioning
confidence: 60%
“…In a previous study, 6 out of 17 patients carrying one of the already published FGF12 variants showed a partial response to phenytoin or lamotrigine, sodium channel blockers that enhance the channels' fast inactivation by shifting voltage-dependence towards more hyperpolarized potentials. 16 However, not all patients responded well to phenytoin, suggesting that these variants may have an additional effect which could not be identified until now. This hypothesis is supported by the FGF12 mouse variant model fgf12 R52H/+ which suffers from spontaneous seizures and dies of sudden unexplained death in epilepsy (SUDEP) at around 16 days of age.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation